Electronic Band Transitions in γ-Ge3N4 - Feldbach, Eduard; Zerr, Andreas; Museur, Luc; Kitaura, Mamoru; Manthilake, Geeth; Tessier, Franck; Krasnenko, Veera; Kanaev, Andrei (Korean Institute of Metals and Materials, 2021)
Electronic band structure in germanium nitride having spinel structure, γ-Ge3N4, was examined using two spectroscopic techniques, cathodoluminescence and synchrotron-based photoluminescence. The sample purity was confirmed by x-ray diffraction and Raman analyses. The spectroscopic measurements provided first experimental evidence of a large free exciton binding energy De≈0.30 eV and direct interband transitions in this material. The band gap energy Eg = 3.65 ± 0.05 eV measured with a higher precision was in agreement with that previously obtained via XES/XANES method. The screened hybrid functional Heyd–Scuseria–Ernzerhof (HSE06) calculations of the electronic structure supported the experimental results. Based on the experimental data and theoretical calculations, the limiting efficiency of the excitation conversion to light was estimated and compared with that of w-GaN, which is the basic material of commercial light emitting diodes. The high conversion efficiency, very high hardness and rigidity combined with a thermal stability in air up to ~ 700 °C reveal the potential of γ-Ge3N4 for robust and efficient photonic emitters. © 2021, The Korean Institute of Metals and Materials. Published under the CC BY license.
This work has been carried out within the framework of the EUROfusion Consortium and has received funding from the Euratom research and training programme 2014-2018 and 2019-2020 under grant agreement No 633053. The views and opinions expressed herein do not necessarily reflect those of the European Commission. Support from Estonian Research Council grant PUT PRG 619 is gratefully acknowledged. The multi-anvil experiments at LMV were supported by the French Government Laboratory of Excellence initiative no ANR-10-LABX-0006, the Région Auvergne and the European Regional Development Fund (ClerVolc Contribution Number 478).
Keywords: Research Subject Categories::NATURAL SCIENCES; Cathodoluminescence; Electronic transitions; Exciton; Photoluminescence; γ-Ge3N4